Retro-Prospective Analysis of Indigenous Ecological Narratives: Ecosemiotic-Cultural Perspectives on Sustainable Development - Efendi, Agik Nur; Ahmadi, Anas; Indarti, Titik; Kurniawati, Erika; Sya’adah, Himatus; Sanubarianto, Salimulloh T; Sa’diyah, Ilmatus; Rokhmawati, Zahro (IAIN Madura, 2025)
This study explores the role of indigenous ecological narratives in shaping sustainable environmental practices through an ecosemiotic-cultural perspective. By employing a retro-prospective analysis, the research examines traditional ecological knowledge embedded in Indonesian literary texts, revealing how past wisdom informs contemporary and future environmental consciousness. The primary data for this research comprises three contemporary Indonesian novels that encapsulate indigenous ecological wisdom and human-nature relationships: Mata dan Manusia Laut (2019) by Okky Madasari, Tanjung Kemarau (2020) by Royyan Julian, Sanggarguri (2021) by Lalu Agus Fathurrahman. The findings demonstrate that indigenous narratives function as semiotic systems that encode ecological values, communal responsibility, and harmonious relationships with nature. Through cultural symbols, myths, and folklore, these narratives offer sustainable models of environmental stewardship rooted in collective memory and local traditions. The study also highlights the potential of integrating these narratives into modern sustainability policies and education, ensuring their relevance in addressing contemporary ecological challenges. By bridging historical ecological wisdom with future sustainability efforts, this research contributes to the broader discourse on ecosemiotics and sustainable development. The implications of this study underscore the significance of interdisciplinary approaches in preserving cultural heritage while fostering environmental resilience.